2019
DOI: 10.3390/s19092204
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Treadmill Walking on Gait and Upper Trunk through Linear and Nonlinear Analysis Methods

Abstract: Treadmills are widely used to recover walking function in the rehabilitation field for those patients with gait disorders. Nevertheless, the ultimate goal of walking function recovery is to walk on the ground rather than on the treadmill. This study aims to determine the effect of treadmill walking on gait and upper trunk movement characteristics using wearable sensors. Eight healthy male subjects are recruited to perform 420-m straight overground walking (OW) and 5 min treadmill walking (TW), wearing 3 inerti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 38 publications
0
24
2
Order By: Relevance
“…In the analysis of the obtained results, it should be taken into account that characteristics of gait with the use of various NW poles (as well as without poles) might be different as in case of gait realized on a different surface. Shi et al [33] observed differences in the structure of movement during over-ground walking and treadmill walking. They found shorter stride length, less stride time, and a reduced correlation between gait and upper trunk features on a treadmill.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the analysis of the obtained results, it should be taken into account that characteristics of gait with the use of various NW poles (as well as without poles) might be different as in case of gait realized on a different surface. Shi et al [33] observed differences in the structure of movement during over-ground walking and treadmill walking. They found shorter stride length, less stride time, and a reduced correlation between gait and upper trunk features on a treadmill.…”
Section: Discussionmentioning
confidence: 99%
“…It is an open question whether there is a difference in the kinematics of gait with or without NW poles as well as whether applied training influenced on biomechanical characteristics of gait realized in everyday life. Shi et al [33] suggested that changes in gait in nonstandard conditions might be related to fall risk prevention, which is very important among older people. Undoubtedly, it is an important direction for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…They introduced a score called Comprehensive Gait Assessment using InerTial Sensor score (C-GAITS score). Effect of treadmill walking on upper trunk and gait are studied in [40] where they engaged eight subjects. Mun et al [21] introduced a CNN-based model to analyze gait estimation from various foot parameters.…”
Section: Related Workmentioning
confidence: 99%
“…Further, within in-lab settings, it has been demonstrated that gait irregularity can differ between non-frail and pre-frail older adults (21). We used Sample Entropy (SampEn) assessment defined as equation (2), where was defined as the number of matches in the filtered acceleration signal length (distance function smaller than tolerance ) and as the number of matches of length ( ) (50)(51)(52)(53)(54).…”
Section: Continuous Walking Boutsmentioning
confidence: 99%